Continuous high-fat high-sugar diet overrides the therapeutic potential of fecal microbiota transplantation from exercised and/or inulin-conditioned donors in obese mice - Masato Kawashima; Takafumi Aoki; Hiroki Hamada; Chihiro Watanabe; Eri Oyanagi; Takumi Kono; Takashi Yamagata; Nicholas P. West; Hiromi Yano (PLoS ONE, 2026)
Fecal microbiota transplantation (FMT) is a promising therapeutic strategy for obesity and related metabolic disorders. Exercise and dietary fiber intake, such as inulin supplementation, have been shown to differentially modulate the gut microbiota and synergistically improve metabolic health. The present study aimed to investigate whether FMT from lean donor mice subjected to voluntary exercise and/or inulin supplementation could ameliorate metabolic dysfunction in high-fat high-sugar diet (HFHSD)-induced obese mice. Four-week-old male C57BL/6J mice were fed HFHSD throughout the experimental period and assigned to one of five groups: sham FMT, FMT from sedentary donors, from exercised donors, from inulin-supplemented donors, or from donors receiving both interventions. Following 12 weeks of obesity induction, mice were treated with antibiotics and then underwent a 4-week FMT protocol. Physical and metabolic parameters, gut microbial composition, and cecal short-chain fatty acid (SCFA) levels were examined in both donors and recipients. The results demonstrated that FMT from exercised and/or inulin-supplemented donors failed to improve obesity-related phenotypes or glucose intolerance in recipients. These outcomes were accompanied by only partial alterations in gut microbiota and SCFA profiles. Collectively, our findings suggest that persistent HFHSD exposure compromises the colonization and function of beneficial microbes, limiting the metabolic benefits of FMT. Successful application of FMT in severe obesity may require prior optimization of the host intestinal environment through dietary interventions or microbiome-targeted strategies.